PERAN DAN TANTANGAN GURU PENDIDIKAN AGAMA ISLAM DALAM PUBLIKASI ILMIAH DI ERA DIGITAL - Aprianti, Aprianti; Albakhar Anshor, Muhammad Farouk; Citra Dewi, Desy Eka (Intiqad: Jurnal Agama dan Pendidikan Islam, 2024)
This study aims to identify the role of PAI teachers in addressing the challenges of the digital era and to examine how they can leverage technology to enhance the quality of learning and scholarly publications. The research employs a qualitative approach with a descriptive analysis, involving a literature review and interviews with PAI teachers in several schools. The findings indicate three main focuses in global digital community-based learning: (1) the construction of inquiry and discovery, (2) creativity and initiative, and (3) interaction and collaboration. Additionally, PAI teachers play seven key roles in digital learning, namely as: (a) sources of learning, (b) facilitators, (c) managers, (d) demonstrators, (e) mentors, (f) motivators, and (g) evaluators. The main challenges faced by PAI teachers include effectively managing scientific information and maintaining the quality of publications.